Taxonomy and Pharmacognostic studies of Tarchonanthus camphoratus species complex (Tarchonanthea, Asteraceae) - Aro, Abimbola (University of Limpopo (Medunsa Campus), 2010)
Taxonomy and Pharmacognostic studies of Tarchonanthus camphoratus species complex (Tarchonanthea, Asteraceae) The genus Tarchonanthus belongs to the family Asteraceae, the subfamily Cichorioideae and the tribe Tarchonantheae. Tarchonanthus is one of the few Astareceae genera that includes a tree. Furthermore, it is dioecious, with male and female flowers produced on different plants. The specific name is usually chosen to indicate some striking characteristics of the plant. The name camphoratus refers to the strong smell of camphor given off when the leaves are crushed. Various parts of Tarchonanthus species are used medicinally. Infusions and tinctures of the leaves and twigs are used for stomach trouble, abdominal pain, headache, toothache, asthma, bronchitis and inflammation. The main aim of this study was to improve the overall knowledge available on Tarchonanthus camphoratus and T. parvicapitulatus by resolving the uncertainties surrounding the taxonomy and also to check for the toxicity and the therapeutic effect of this plant. A micromorphological and solubility studies proved useful in distinguishing between T. camphoratus and T. parvicapitulatus since the macromorphological characteristics of the plant did not prove useful due to overlapping keys used to distinguish the two species. A solubility studies also proved useful in differentiating between male, female or sterile plants of T. camphoratus and T. parvicapitulatus. The results that were obtained from the TLC plates showed that there are differences in the chemical composition of the acetone extracts of T. camphoratus and T. parvicapitulatus. Moreso, this study showed that the acetone extract of T. parvicapitulatus has more antioxidant properties than T. camphoratus. The therapeutic study also revealed that the plant extract from the leaves of T. camphoratus and T. parvicapitulatus showed no prophylactic protection against smooth muscle contraction of guinea-pig treachea but the plant extract of T. parvicapitulatus could relax pre-existing smooth muscle contraction of guinea-pig trachea. Superoxide production was significantly inhibited by both T. parvicapitulatus and T. camphoratus plant extract, but the rate of superoxide inhibition of T. parvicapitulatus extract were more prominent than it was for T. camphoratus extract. The inhibitory effects of the water extract of T. camphoratus and T. parvicapitulatus on the isolated human neutrophils could be due to the activity of the intermediate polar compounds which include flavonoids. This explains why these plant extracts are used by traditional healers for the relieve of ailments such as abdominal pain, headache, toothache T. parvicapitulatus are toxic but the plant extracts of T. camphoratus did not show significant toxicity to isolated human neutrophils. This study has helped to improve the overall knowledge available on Tarchonanthus camphoratus and Tarchonanthus parvicapitulatus by using different pharmacognostic tools to resolve the uncertainties surrounding the taxonomy and to determine the toxicity and the therapeutic effects of this plant.
Thesis (Msc.(Pharmacology))--University of Limpopo, 2010.
Keywords: Taxonomy; Pharmacognostic; Asterciceae